FACTOR ANALYSIS OF STUDENTS' INTRINSIC MOTIVATION IN LEARNING ENGLISH - Risda; Andi Asri Jumiati; Uyunnasirah Hambali (FKIP Unismuh Makassar, 2022)
The objective of this research was to find out the factors that can influence students’ intrinsic motivation in learning English. This research was in descriptive quantitative method. The population of this research was the students of SMPN 2 Binongko, namely first grade. By applying simple random sampling technique, the sample of this research was 6 students from the first grade. Research instrument used for collecting the data was questionnaire. It consisted of 10 items about intrinsic motivation.The result showed that, in this research researcher analyzed factors that can influence students’ intrinsic motivation in learning English by intrinsic motivation is self-confidence that is owned by each students. The data students’ intrinsic motivation was 55.92% in the first grade.